2016
DOI: 10.1007/s11897-016-0280-1
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in Heart Failure: Are There Gender Differences?

Abstract: Compared to men, women with heart failure (HF) are often older, smoke less, and have more preserved ejection fraction (EF) and hypertensive HF rather than HF of ischemic etiology. Gender-stratified outcomes on comorbidities data in HF are scarce. Women have traditionally been underrepresented in HF trials. Although data suggest that overall prognosis may be better in women, they experience lower quality of life with greater functional impairment from HF compared to men. Gender differences have been reported fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
29
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 117 publications
4
29
2
Order By: Relevance
“…Men with heart failure are more often smokers and more likely to have MI, COPD and heart failure with reduced ejection fraction. 34 Our findings are consistent across many of these comorbidities; however, we found lung disease to be more common in women. Whether this is due to sex differences in smoking rates, and uptake and compliance with smoking cessation programs is not known.…”
Section: Discussionsupporting
confidence: 79%
“…Men with heart failure are more often smokers and more likely to have MI, COPD and heart failure with reduced ejection fraction. 34 Our findings are consistent across many of these comorbidities; however, we found lung disease to be more common in women. Whether this is due to sex differences in smoking rates, and uptake and compliance with smoking cessation programs is not known.…”
Section: Discussionsupporting
confidence: 79%
“…Concurrent medical comorbidities, such as respiratory diseases and obesity, may also affect interpretation of symptom severity. 6 For chronic HF with reduced ejection fraction (HFrEF), studies have found that NYHA class IV compared with NYHA class III is a predictor of mortality in women but in not men. 7 This raises the possibility that the underlying pathophysiology and risk factors for HF may be sex specific.…”
mentioning
confidence: 99%
“…There are, however, controversies regarding the effect of sex on the prevalence of chronic renal failure and diabetes, with contradictory results in the literature [25,32,[36][37][38][39]. The significant differences shown in COPD prevalence could be associated with higher levels of tobacco use in men [6,11,25], since toxic habits were clearly more frequent in men (although probably under-registered), as previously reported in the literature [8,11,26]. On the other hand, women were more likely to suffer conditions such as depression, osteoporosis, osteoarticular pathology, varicose veins, hypothyroidism, and asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure presents, in most cases, as a chronic disease with a high burden of comorbidities, some of which seem to be sex-specific [6]. Whereas women are more likely to present comorbid hypertension, diabetes, hypothyroidism, obesity, and depression, men tend to have more peripheral vascular disease, ischemic heart disease and chronic obstructive pulmonary disease (COPD) [9,11,12]. The overall constellation of comorbidities surrounding HF may play an important role not only in the pathophysiology, but also in the treatment and prognosis of the disease [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation